A better way to throw the discus? - Atwaa, M.; Gamal, M.; Sakr, M. (Track Coach, 2018)
The aim of throwing the discus is to achieve the greatest horizontal distance as possible. Each phase of technique has its role in the resultant performance. The general trend of training programs is to improve physical fitness in order to increase the resultant distance. The authors aimed to modify throwing technique as a way to achieve greater distances in the discus throw event, in a way that doesn't conflict with IAAF-certified throwing technique. The study was descriptive and empirical, while a comparison in some kinematical aspects was carried on between two discus trials. One was performed with the current style and the other was performed with the modified style. The participant was an Egyptian elite decathlon athlete. The results emphasized the advantages of using the modified technique, due to the mechanical advantages achieved.